2009
DOI: 10.4490/algae.2009.24.3.149
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Benthic Chlorophyll a and Sediment Properties in the Tidal Flats of Kwangyang Bay, Korea

Abstract: Characteristics of benthic microalgae and sediment properties were investigated for the intertidal flats of Kwangyang Bay, Korea. Sampling stations were selected every 100 m in the intertidal flats from land-side to open ocean at two different sampling sites. Samples were collected in June 2004, July, September, November, February and May 2005. Sediments properties were measured including temperature, water contents, sediment bulk density, nutrient concentrations in porewater. Chlorophyll a concentrations in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…On the opposite, others authors suggest that it depends on the amount of organic matter produced, since nutrients are released during decomposition (Burdige, 2006). NH 4 + concentrations in porewater recorded here are lower than those found in other works from the Bahía Blanca Estuary (Spetter, 2006;Marcovecchio et al, 2009;Negrin et al, 2011) and from others tidal flats in the world (Magni and Montani, 2006;Sin et al, 2009). On the contrary, NO 3 À values from both sites were in general higher than the ones usually found in other sites of the estuary without microbial mats (Spetter, 2006;Marcovecchio et al, 2009).The high NO 3 À concentrations could be associated with the possible input of nutrients from groundwater (Galloway, 2005), which has not been studied in the area so far, but the groundwater presence has been reported by Cuadrado et al (2013a) at the study site.…”
Section: Nutrients In Porewatercontrasting
confidence: 75%
“…On the opposite, others authors suggest that it depends on the amount of organic matter produced, since nutrients are released during decomposition (Burdige, 2006). NH 4 + concentrations in porewater recorded here are lower than those found in other works from the Bahía Blanca Estuary (Spetter, 2006;Marcovecchio et al, 2009;Negrin et al, 2011) and from others tidal flats in the world (Magni and Montani, 2006;Sin et al, 2009). On the contrary, NO 3 À values from both sites were in general higher than the ones usually found in other sites of the estuary without microbial mats (Spetter, 2006;Marcovecchio et al, 2009).The high NO 3 À concentrations could be associated with the possible input of nutrients from groundwater (Galloway, 2005), which has not been studied in the area so far, but the groundwater presence has been reported by Cuadrado et al (2013a) at the study site.…”
Section: Nutrients In Porewatercontrasting
confidence: 75%
“…The highest Chl a content was also recorded in spring at site 7, while the lowest content was found in winter at site 1 ( Figure 8B). These results coincide with findings of Underwood and Paterson (1993), Santos, Pastel, and Souza-Santos (1997) and Sin, Ryu, and Song (2009) who reported that epipelic biomass represented by Chl a often shows the seasonal patterns of increase during the summer months or throughout the year, even in winter. The highest density of macroinvertebrates (approximately 30,000 ind./cm 2 ), in turn, was recorded in spring at site 6 ( Figure 9).…”
Section: Spatial and Temporal Distributions Of Benthic Algae And Macrsupporting
confidence: 91%
“…Effective number of species was also significantly influenced by temperature and sediment characteristics, i.e., mean grain size and mud content. The negative relationship with temperature supported previous findings that show that warmer temperatures often favor dominance of certain MPB groups (Sin et al, 2009;Cartaxana et al, 2015;Ribeiro et al, 2021), whereas diatoms thrive only at lower temperatures (Watermann et al, 1999;Underwood, 2001;Scholz and Liebezeit, 2012b). Janousek (2009) and Semcheski et al (2016) reported higher MPB diversity in muddy sediments than in sandy sediments, a result of the depository nature of more protected muddy sites, and higher resistance of MPB biofilms on muddy sediments against erosion (Cahoon et al, 1999;Herman et al, 2001).…”
Section: Environmental Factors Mpb Biomass and Pigment Diversity Patt...supporting
confidence: 88%